Pengaruh Pengendalian Emosi dan Aktivitas Spiritual terhadap Kinerja Guru (Studi Empiris pada Guru di Islamic Boarding School SMP Ar-rohmah Putri di Malang) - Sudiro, Achmad (Jurnal Aplikasi Manajemen, 2009)
This aims of the research is to test the impact between emotional control and spiritual activity toward performance of the teachers. Data collecting conducted by disseminating questionnaire. Respondent of the research is the fifty seven respondents in this research were the whole teacher at the Islamic boarding school SMA Ar-Rohmah Putri in Malang. Based on multiple linear regression analysis showed coefficient determination of adjusted R Square (Adjusted R2) at .755. the Ftest showed at 40.958 > from Ftable 3.4028 had effected significantly, where Ftest < 5% (.000 < .05). ttest showed emotional control variable has ttest 2.5 > from ttable 2.0369 had effected significantly, where t < .05 (.000 < .05).The research showed the following results: emotional control and spiritual activity simultaneously and partially effect significantly toward performance of the teachers. In addition, this research showed spiritual activity has dominant effect toward performance of the teachers at Islamic Boarding School SMP Ar-Rohmah Putri in Malang.